THERMAL MODEL OF ENERGY EFFICIENT BUILDING - E. V. Kresova; S. P. Kundas (Informatika)
Thermal 3-D model of a rural area building is proposed. The model includes constructive, finite element, analytical and computational models which are created using SolidWorks software (constructive model) and COMSOL Multiphysics software (finite element, analytical and computational models). An additional object was created for modeling heat transfer process in the whole volume of building. Studies have shown model efficiency and possibility of its application for optimizing building isolation.